Correlation between Learning Interest with Student's Learning Achievement in Islamic Religion (Case Study of MTs.S Teupah Barat) - Afriani S; Ayel Sarwono Lahra; Trisosiana Lefia; Siti Lesnita (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Interest is a tendency to pay attention continuously, which serves as a force that will encourage someone to learn. Students who are interested in the lesson will be seen students to be diligent in learning. The role of interest is to improve student learning achievement. If students have a high interest, their level of learning achievement will produce high scores. Learning achievement is evidence of the efforts that have been made in teaching and learning activities and is the value obtained by students from the learning process that has been taken. The formulation of the problem in this study is "Is there a relationship between interest in learning and student achievement in Islamic Religious Education (PAI) class VII (seven) West Teupah. The research hypothesis in this study is "There is a relationship between interest in learning and learning achievement in Islamic Religious Education (PAI) at MTs.S Teupah Barat" The research that the researchers did was quantitative research, the population was 25 students, the authors took a sample of 5% of 25 students so that the sample taken is 25 students. The sampling technique used is simple random sampling by means of lottery. Data collection methods used are questionnaires and documentation. Based on the analysis, the data obtained using the calculation of the Product Moment Correlation, the price of the Product Moment Correlation (r_xy) = 0.000, while the price of ab???????? in the table with a significant level of 5%. Based on these results, the Product Moment Correlation (r_xy) is smaller than the price ab????????, so the alternative hypothesis (Ha) is not accepted. It can be concluded that there is no relationship between interest in learning and student achievement in Islamic Religious Education class VII (seven) at MTs.S Teupah Barat.